2014
DOI: 10.1002/dc.23188
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of ThinPrep preparation in the assessment of fine‐needle aspiration biopsy of salivary gland neoplasms

Abstract: ThinPrep may be considered as another practical method of specimen preparation in the assessment of salivary gland neoplasms, particularly when FNA is performed without immediate assistance from cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…In these two studies, the proportion of ND cytology was determined to be higher in TP samples compared to CSs. Hipp et al evaluated 178 nonsplit‐sample TP preparations and the ND rate was reported to be 40% for TP samples. In the current study, while ND aspirates constituted 16.1% of 459 liquid‐based preparations, this rate was 7% of 129 follow‐up patients in nonsplit‐samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these two studies, the proportion of ND cytology was determined to be higher in TP samples compared to CSs. Hipp et al evaluated 178 nonsplit‐sample TP preparations and the ND rate was reported to be 40% for TP samples. In the current study, while ND aspirates constituted 16.1% of 459 liquid‐based preparations, this rate was 7% of 129 follow‐up patients in nonsplit‐samples.…”
Section: Discussionmentioning
confidence: 99%
“…The smears are stained with Giemsa, hematoxylin–eosin, and/or Papanicolaou stains. The sensitivity and specificity rates of salivary gland FNAs have been reported as 63%‐93% and 90%‐100%, respectively, when using CS preparations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Hipp et al [4] reported their review of 369 FNA of salivary gland aspirates with neoplastic follow-up. Of these, 178 were processed by TP only and 191 were processed by CS only or in combination with TP.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology has several advantages over conventional smears (CS), including the following: (1) more standardized processing, especially with samples received from outside clinics or shipped from a distance to centralized laboratories; (2) decreased screening area; (3) decreased obscuring material such as blood, inflammation and mucus; (4) lack of air-drying artifacts; (5) a more monolayer cellular surface that is easier to screen; (6) consistently well-preserved cells, and (7) the potential for automated screening in LBC specimens [1,2,3,4]. Because of the many advantages of LBC, the technique has been increasingly adopted by many laboratories for nongynecological specimens, particularly exfoliative samples.…”
Section: Introductionmentioning
confidence: 99%